My lover, the rabbi : a novel - Koestenbaum, Wayne (FSG Originals / Farrar, Straus and Giroux, 2026)
"By Guggenheim Fellow and Distinguished Professor at the CUNY Graduate Center Wayne Koestenbaum, a novel chronicling the increasingly obsessive psychosexual relationship between a rabbi and the man devoted to him, an entanglement with unpredictable consequences for the two men and those around them"-- Provided by publisher.